Cardiovascular adjustments during experimentally induced retraction and locomotion in the invasive terrestrial snail Cornu aspersum (Müller, 1774) - Edgar Alejandro Pardo-Sarmiento; Juan Pablo Hernández; Natalia Buitrago-Ricaurte; Andre J. Riveros (PLoS ONE, 2026)
The coupled function of physiology and behavior is crucial for generating survival responses. Generally, the cardiovascular system undergoes rapid adjustments during scape behavior to increase oxygen delivery to muscle tissues. In contrast, passive antipredator responses such as retraction in snails may impose mechanical constraints on the circulatory system. Here, we evaluated the cardiovascular response underlying the scape response (through induced retraction) and the physical activity in the invasive land snail Cornu aspersum . We quantified heart rate and heart rate variability in adult snails using laser optocardiography under the two conditions. We found that heart rate increased from retracted to the moving state and was accompanied by changes in heart rate variability and reduction of cardiac irregularities. Also, we found that locomotion intensity and body size did not influence these cardiac parameters. Our results suggest that metabolic demands, neural regulation and mechanical configuration collectively alter heart rate and heart rate variability. Thus, cardiovascular function is strongly dependent on behaviorally induced mechanical shifts in the circulatory system and on a “fight-or-flight”-like response.